Two new species of Timonius (Rubiaceae: Guettardeae) from the Malay Peninsula - Hoo, Pui Kiat; Sugumaran, Manickam; Wong, Khoon Meng (Phytotaxa, 2023)
Two new species of Timonius endemic to the Malay Peninsula are described and illustrated: T. megalocalyx and T. denigricans, and their distribution and ecology discussed. Both species have been thought to be conspecific with their most resembling taxa in a previous revision but are here shown to be distinct.